CUSTOMERS' INTENTION TO USE SHARIA FAMILY INSURANCE - Sumadi, Sumadi; Muslichah, Istyakara (JBFEM, 2018)
Risk is unpredictable thing that people want to avoid or minimize it. Sharia family insurance is one of the alternatives that can be used to minimize risk. However, Indonesian people, known as the largest Muslim population, are selective in deciding whether to use the sharia or conventional one. Thus, this research aims to analyze the factors that influence customers’ intention to use sharia family insurance. This study was conducted using quantitative approach with survey method and data was collected using questionnaire. The survey involved 180 respondents. Using judgment sampling, the respondents were married people who have sharia family insurance. Data was analyzed using SEM. There are four proposed factors (protection, investment, WOM referents, media referents) that influence intention to use sharia family insurance mediated by attitude or subjective norm. However, protection was not significant to influence that relationship. This study is expected to give a brief view and insight for parties involved in sharia insurance industry to give better service and to attract more customers.